2012
DOI: 10.1016/j.neurobiolaging.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesions and brain gray matter volume in cognitively normal elders

Abstract: Objectives Cerebral white matter lesions (WMLs) reflect small vessel disease, are common in elderly individuals and are associated with cognitive impairment. We sought to determine the relationships between WMLs, age, gray matter (GM) volume, and cognition in the Cardiovascular Health Study (CHS). Methods From the CHS we selected 740 cognitively normal controls with a 1.5 T MRI scan of the brain and a detailed diagnostic evaluation. WML severity was determined using a standardized visual rating system. GM vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
105
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 62 publications
(88 reference statements)
22
105
0
1
Order By: Relevance
“…These data suggest that brain atrophy is part of the SVD pathological spectrum and is not a coincidental finding, a conclusion supported by the Cardiovascular Health Study. 13 Similar findings were recently reported by the SMART-MR Study (Second Manifestations of Arterial Disease-Magnetic Resonance).…”
Section: Brain Atrophy In Association With Vcisupporting
confidence: 84%
“…These data suggest that brain atrophy is part of the SVD pathological spectrum and is not a coincidental finding, a conclusion supported by the Cardiovascular Health Study. 13 Similar findings were recently reported by the SMART-MR Study (Second Manifestations of Arterial Disease-Magnetic Resonance).…”
Section: Brain Atrophy In Association With Vcisupporting
confidence: 84%
“…A higher vulnerability of frontal white matter to vascular disease plays a crucial role in deficits of executive function and attention due to frontal-subcortical disconnection [18]. A prior brain structural study also showed that the WMLs were inversely correlated with the volume of grey matter, with the greatest volume loss in the frontal cortex [19]. Furthermore, a close relationship between FA and executive function in the frontal was also performed and FA may provide an early valuable index to detect age-related cognitive decline [20].…”
Section: Discussionmentioning
confidence: 99%
“…Each of these changes can individually be related to an increased, albeit small, dementia risk; however, when combined, they produce additive effects on function. 11,24,25 It has also been suggested that many changes are interrelated, for example, more severe white matter damage and vascular lesions are associated with more severe gray matter and hippocampal atrophy, [26][27][28] producing a combined effect on cognition, though the relationships typically are nonlinear. 29,30 By combining these changes, their overall effect can be understood more comprehensively.…”
Section: Discussionmentioning
confidence: 99%